4(m+2)=

Simple and best practice solution for 4(m+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(m+2)= equation:


Simplifying
4(m + 2) = 0

Reorder the terms:
4(2 + m) = 0
(2 * 4 + m * 4) = 0
(8 + 4m) = 0

Solving
8 + 4m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 4m = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 4m = 0 + -8
4m = 0 + -8

Combine like terms: 0 + -8 = -8
4m = -8

Divide each side by '4'.
m = -2

Simplifying
m = -2

See similar equations:

| 6y^2-y-12=0 | | x+8=2(x+24) | | 6(a+3)-15= | | 4(m-2)+2(3m+2)= | | 8x-16=4x-4 | | 525+0.21x=850 | | 11x+5=4x+9 | | x+6=40 | | 13(4x-7)=13 | | 8(3x+6)=96 | | 2(x+7)=56 | | s^2+s+4=0 | | 71-6x=35 | | 22+4x=50 | | y^2-4= | | 5x-73=27 | | 2Y^3-Y+3X-2=0 | | 6x+29=13x+41 | | s^2-s+4=0 | | (6x-7)+9x=68 | | 10x-117=5x-7 | | 8x^7y(5x^6y^2-6x^2+4y^3)= | | 5(2y+4)= | | -2+3(x-9)-2(x+3)=0 | | 2z^2+40=-8z | | 4+x=117 | | p+4p=60 | | 5x^2+30x-10=0 | | 3n+5=n-8 | | 3y(2y-4)=16 | | 3y(2y-4)=21 | | log*x^2-log*x=log*100 |

Equations solver categories